Targeting Thymidylate Synthase Enhances the Chemosensitivity of Triple-Negative Breast Cancer Towards 5-FU-Based Combinatorial Therapy - Haritha, Nair Hariprasad; Nawab, Akbar; Vijayakurup, Vinod; Anto, Nikhil Ponnoor; Liju, Vijayasteltar B.; Alex, Vijai V.; Amrutha, Areekkara Nisthul; Aiswarya, Sreekumar U.; Swetha, Mundanattu; Vinod, Balachandran S.; Sundaram, Sankar; Guijarro, Maria V.; et al. (Frontiers in Oncology, 2021)
Background: The ongoing treatment modalities for breast cancer primarily rely on the expression status of ER, PR and HER-2 receptors in breast cancer tissues. Our strategy of chemosensitization provides new insights to counter chemoresistance, a major obstacle that limits the benefits of chemotherapy of mammary cancers. Methods: By utilizing a murine breast cancer model employing NSG mice bearing orthotopic triple-negative breast cancer xenografts, we have evaluated the ability of phytochemical curcumin in chemosensitizing breast cancer to 5-FU chemotherapy and the differential modulations of cellular events in response to this strategy, independent of their receptor status. Results: A significant synergistic antitumor potential was observed in the murine model with a sub-optimal dose treatment of 5-FU plus curcumin, as evaluated by a reduction in the tumor-related parameters. We authenticated the pivotal role of thymidylate synthase in regulating the 5-FU–curcumin synergism using the TNBC pre-clinical model. Our study also confirmed the pharmacological safety of this chemotherapeutic plus phytoactive combination using acute and chronic toxicity studies in Swiss albino mice. Subsequently, the molecular docking analysis of curcumin binding to TS demonstrated the affinity of curcumin towards the cofactor-binding site of TS, rather than the substrate-binding site, where 5-FU binds. Our concomitant in vivo and in silico evidence substantiates the superior therapeutic index of this combination. Conclusion: This is the first-ever pre-clinical study portraying TS as the critical target of combinatorial therapy for mammary carcinomas and therefore we recommend its clinical validation, especially in TNBC patients, who currently have limited therapeutic options.